2019
DOI: 10.1371/journal.pone.0210576
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile and hepatoprotective effect of Aeschynomene elaphroxylon (Guill. & Perr.)

Abstract: Liver diseases are life-threatening and need urgent medical treatments. Conventional treatment is expensive and toxic, so the urge for nutraceutical hepatoprotective agents is crucial. This study is considered the first metabolic profile of Aeschynomene elaphroxylon (Guill. & Perr.) extracts of; flowers, leaves & bark adopting UPLC-Orbitrap HRMS analysis to determine their bioactive metabolites, and it was designed to investigate the potential hepatoprotective activity of A. elaphroxylon flowers and bark extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…ROS prompts OS that can cause extreme cell damage, in this way prompting pathogenesis of numerous other remarkable diseases . The present examination affirms an expansion in the lipid peroxidation (LPO) level in CCl 4 ‐directed rodents, which is seen in their hepatic tissue (estimated as MDA), which uncovered the liver cells to oxygen‐free radicals . Moreover, these obtained outcomes are similar to the result of a past examination led on comparable topics.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…ROS prompts OS that can cause extreme cell damage, in this way prompting pathogenesis of numerous other remarkable diseases . The present examination affirms an expansion in the lipid peroxidation (LPO) level in CCl 4 ‐directed rodents, which is seen in their hepatic tissue (estimated as MDA), which uncovered the liver cells to oxygen‐free radicals . Moreover, these obtained outcomes are similar to the result of a past examination led on comparable topics.…”
Section: Discussionsupporting
confidence: 87%
“…37,38 The present examination affirms an expansion in the lipid peroxidation (LPO) level in CCl 4directed rodents, which is seen in their hepatic tissue (estimated as MDA), which uncovered the liver cells to oxygenfree radicals. 39,40 Moreover, these obtained outcomes are similar to the result of a past examination led on comparable topics. CCl 4 has the ability to prompt the generation of reactive oxygen-free radicals, for example, H 2 O 2 , 41,42 superoxide anions and hydroxyl radicals.…”
Section: Discussionsupporting
confidence: 81%
“…Oxidative stress is a key mechanism inducing cytotoxicity through enhancing the production of MDA accompanied by depletion of GSH in tissues; these are considered the most important indexes of antioxidant activities 42. This may be a mechanism for the toxicity of NPs 43,44.…”
Section: Discussionmentioning
confidence: 99%
“…This revealed that MEJSL could possess hepatoprotective effect. It has been previously shown that elevated plasma AST and ALT activities are indicators of tissue damage which are measured clinically as a diagnostic evaluation of liver function [44]. Hepatocellular damage resulting from formaldehyde-induced oxidative and inflammatory stressors could cause leakage of cytoplasmic enzymes into the plasma with concomitant increase in plasma enzyme activities.…”
Section: Discussionmentioning
confidence: 99%